Digitalization and Society (Edition 1) - Ayhan, Bünyamin (Peter Lang International Academic Publishing Group, 2017)
This book presents a collection of papers by researchers from several different institutions on a wide range of digital issues.Digitalization describes the phenomenon of how knowledge is processed and the processed knowledge provides social transformations beyond digitization, interaction, annihilation of time and space, the phenomenon of usage in multimedia. Transformed is not only the society but also its mentality. Digitalization reveals a sui generis digimodern process by processing modern structures with the help of compulsory tools. This process is a reconstruction of social structures and institutions on the basis of the digitalization perspective. Each social institution adapts this process and provides a contribution to the digitalization of society.